P98 Predictors of early hepatic artery thrombosis after primary liver transplantation: a cohort multi-centre study. (16th November 2010) - Dawwas, M; Gimson, A
Abstract : Introduction: Hepatic artery thrombosis (HAT) is one of the most catastrophic complications of liver transplantation. The risk factors for this complication have rarely been assessed in the setting of a large risk-adjusted analysis. Method: Using the United Kingdom and Ireland Liver Transplant Database, we sought to identify the incidence of and independent risk factors for early (=3 months) HAT among 6297 adult first single-organ liver transplant recipients during the period 1 March 1994–31 March 2006. Univariate and multivariable logistic regression models were fitted to examine the association between early HAT and a wide-range of recipient, donor and graft risk factors. Results: The incidence of early HAT in this cohort was 3.6%. Multivariable analysis identified the following independent risk factors for early HAT: recipient diagnosis of hepatocellular carcinoma (OR 1.64 95% CI 1.08 to 2.47), primary sclerosing cholangitis (OR 1.86 95% CI 1.24 to 2.81), recipient requirement for preoperative renal support (OR 1.81 95% CI 1.26 to 2.60), use of reduced vs whole graft (OR 2.53 95% CI 1.40 to 4.57), use of multiple vs single HA anastomosis (OR 1.55 95% CI 1.11 to 2.18), lower donor weight (p<0.001), combination of non-white donor and non-white recipient vs white donor and white recipient (OR 4.67 95%CI 1.41 to 15.47), combination of CMV+ donor and CMV- recipient vs CMV+ donor and CMV+ recipient (OR 1.70 95% CI 1.19 to 2.41), and combination of female donor and female recipient vs male donor and male recipient (OR 1.80 95% CI 1.21 to 2.66). Even after adjustment for the above risk factors, the risk of early HAT was significantly higher in four of the eight liver transplant centres in the UK and Ireland compared to the centre with the lowest incidence, the ORs ranging between 3.5 and 4.6 (p<0.001). Conclusion: Our findings suggest that early HAT is predominantly a technical complication that is independent of recipient, donor and graft characteristics. HAT risk-stratification based on the results of this analysis could help identify patients who may benefit from increased surveillance for this complication and/or institution of appropriate prophylactic antithrombotic therapy.